The role of cancer stem cells and the therapeutic potential of TRX-E-002-1 in ovarian cancer. (3rd August 2018) - Saif, Muhammad; Ager, E. I.; Field, Penelope; Lilischkis, K. J.
ABSTRACT: Introduction : Ovarian cancer is hard to detect and treat. Approximately 70% of epithelial ovarian cancer (EOC) patients are diagnosed at stage III/IV and ~ 75% of these will experience tumor recurrence. Cancer stem cells (CSCs) are implicated in treatment resistance and relapse. Areas covered : The authors examine published data on EOC and ovarian CSCs and discuss the potential of anti-CSC strategies, focusing on non-clinical data supporting the phase 1 clinical trial of TRX-E-002–1 for EOC. The challenges facing anti-CSC strategies are also discussed. Expert opinion : The potential of TRX-E-002–1 treatment to benefit EOC patients is based on its ability to target both differentiated and CSC populations. However, a key challenge will be defining relevant endpoints to allow assessment of anti-CSC activity as early as possible in clinical development and to define populations that will receive most benefit from an anti-CSC strategy.